An investigation into the level of HIV and AIDS awareness among learners in the rural schools of Makhuduthamaga Municipality in Limpopo - Masemola, Mashomanye Kenneth (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2005.